Peningkatan Pemahaman Guru Dengan Pembelajaran Kemampuan Numerasi (PKN) Di SDN Setia Asih 01 - Manurung, Alberth; Halim, Abdul; Muhammad Nur, Syurya (PELITA NUSA TENGGARA, 2025)
Increasing Teacher Understanding by Learning Numeracy Skills (PKN) is a learning model based on solving mathematical problems that uses intelligence so that they are able to face everything that is new and complex. Increasing Teacher Understanding by Learning Numeracy Skills is a model that aims to instill and develop the learning process in teachers. The aim of community service activities is to increase knowledge which changes over time. The subjects of this community service are all teachers at SDN Setia Asih 01. Based on the results of observations, in the learning process teachers still use conventional teaching methods or are centered on the teacher as a provider of information. With the empowerment of teacher skills, it is hoped that students will improve their good numeracy skills from each problem-solving concept in the form of problem applications. Based on this, recommendations for solutions to problems need to be carried out through mentoring activities and increasing teacher understanding by learning numeracy skills both when learning is done at school or studying at home (online). The method used is through socialization, self-reflection and program mapping, measurement and evaluation